Factors Associated with Long-Term Control of Type 2 Diabetes Mellitus - Mohammed Badedi; Yahiya Solan; Hussain Darraj; Abdullah Sabai; Mohamed Mahfouz; Saleh Alamodi; Abdullah Alsabaani (Journal of Diabetes Research)
Aims. This study assessed factors associated with glycemic control among Saudi patients with Type 2 diabetes mellitus (T2DM). Methods. We conducted an analytical cross-sectional study, which included a random sample of 288 patients with T2DM proportional to the diabetes population of each primary health care center in Jazan city, Kingdom of Saudi Arabia. Results. More than two-thirds (74%) of patients had poor glycemic control. Lack of education, polypharmacy, and duration of diabetes ≥ 7 years were significantly associated with higher glycated hemoglobin (HbA1c). Moreover, patients who were smoker or divorced were significantly more likely to have higher HbA1c. The patients who did not comply with diet or take their medications as prescribed had poor glycemic control. The study found lower HbA1c levels among patients who received family support or had close relationship with their physicians. Similarly, knowledgeable patients towards diabetes or those with greater confidence in ability to manage self-care behaviors had a lower HbA1c. In contrast, risk factors such as depression or stress were significantly correlated with poorer glycemic control. Conclusion. The majority of T2DM patients had poor glycemic control. The study identified several factors associated with glycemic control. Effective and tailored interventions are needed to mitigate exposure to these risk factors. This would improve glycemic control and reduce the risks inherent to diabetes complications.